Monitoring and Analysis of Circumferential Pressure for Long‐Distance Pipe Jacking Construction in Composite Strata - Yunfei Zhao; Feilun Luo; Liang Xiong (Engineering Reports)
ABSTRACT At present, the monitoring methods of mechanical parameters of pipe in the process of pipe jacking construction generally have the disadvantages of low data reliability and poor timeliness. Especially in the jacking construction in complex strata, if the jacking parameters and lubrication grouting parameters cannot be adjusted in real time according to the circumferential pressure, it is easy to cause pipe sticking accident. Based on the Inner Mongolia Water Diversion Project from ChaorHe to Liaoning, this paper adopts the LPWA low‐power wide‐area network wireless sensing system based on 5G and IOT technology to realize the real‐time wireless monitoring of the contact pressure and lubrication grouting pressure of the underground pipe jacking pipe. Through the parameters obtained by the wireless sensing system, the stress characteristics of a specific pipe traversing different strata and under different working conditions were studied, and the change rule of circumferential contact pressure of the pipe and the influence of various factors on it were analyzed. The results show that: by analyzing the circumferential contact pressure obtained by the wireless sensing system, the pressure distribution of the pipe in the top soft and bottom hard strata is right>left>bottom>top; in the full‐section strata, the destruction of the lubricating mud sleeve will lead to the same contact pressure on one side and the bottom of the pipe; when the pipe traverse the interfaces of different rock strata, the stability of the lubricating mud sleeve will be affected, and thus the circumferential contact pressure will be altered. The above results are consistent with the theoretical prediction and can provide reference for the actual project. In conclusion, the wireless sensing system can accurately reflect the distribution of circumferential contact pressure of the pipe under different strata, and provide reliable data support for improving construction efficiency and safety.